Does a radio jet drive the massive multiphase outflow in the ultra-luminous infrared galaxy IRAS 10565 + 2448?. Issue 4 (3rd February 2023) - Su, Renzhi; Mahony, Elizabeth K; Gu, Minfeng; Sadler, Elaine M; Curran, S J; Allison, James R; Yoon, Hyein; Aditya, J N H S; Chandola, Yogesh; Chen, Yongjun; Moss, Vanessa A; Wu, Zhongzu; et al.
ABSTRACT: We present new upgraded Giant Metrewave Radio Telescope H i 21-cm observations of the ultra-luminous infrared galaxy IRAS 10565 + 2448, previously reported to show blueshifted, broad, and shallow H i absorption indicating an outflow. Our higher spatial resolution observations have localized this blueshifted outflow, which is ∼ 1.36 kpc southwest of the radio centre and has a blueshifted velocity of $\sim 148\, \rm km\, s^{-1}$ and a full width at half maximum of $\sim 581\, \rm km\, s^{-1}$ . The spatial extent and kinematic properties of the H i outflow are consistent with the previously detected cold molecular outflows in IRAS 10565 + 2448, suggesting that they likely have the same driving mechanism and are tracing the same outflow. By combining the multiphase gas observations, we estimate a total outflowing mass rate of at least $140\, \rm M_\odot \, yr^{-1}$ and a total energy loss rate of at least $8.9× 10^{42}\, \rm erg\, s^{-1}$, where the contribution from the ionized outflow is negligible, emphasizing the importance of including both cold neutral and molecular gas when quantifying the impact of outflows. We present evidence of the presence of a radio jet and argue that this may play a role in driving the observed outflows. The modest radio luminosity $L_{\rm 1.4GHz}\, \sim 1.3× 10^{23}\, {\rm W\, Hz^{-1}}$ of the jet in IRAS 10565 + 2448 implies that the jet contribution to driving outflows should not be ignored in low radio luminosity active galactic nuclei.